A necessidade de um cuidar peculiar na assistência de enfermagem ao idoso vítima de trauma por queda: uma revisão integrativa da literatura - SILVA, Jakelinne de Souza Nazaré da (2019)
OBJECTIVE: Identify the scientific production related to the focus of nursing care for elderly people victims of trauma from falling in the period 2005-2015. METHODOLOGY: An Integrative Review of Literature. The data was collected in the database of the Virtual Health Library Latin American and Caribbean Health Sciences and Scientific Electronic Library Online. RESULTS AND DISCUSSION: In a universe of more than 500 articles, only two contemplated the inclusion criteria. To identify the findings elaborated a data collection instrument gathering: names of the authors, title of the research, methodology, results and inherent thematic considerations to be highlighted. The results revealed the lack of adoption of nurse-specific form of assistance to the elderly life cycle, in the process of caring for the victim of trauma fall, bringing thoughts of the need for adoption of specific protocols and promotion with nursing and nurse association to practice the peculiarities of the aging process, since the fall bring a dim prognosis for the health problems and the possibility of death for the elderly. CONSIDERATIONS: The unveiled incipient points out that nursing care to elderly victims of trauma fall, requires a peculiar attention of the look of the nurse, and necessary approach and pipelines that bring benefits of understanding the aging process and the look of lined nurse in meeting individuality inherent in this cycle of human life.